Study of behavior incentive mechanism of energy conservation and emission reduction for China freshwater live fish supply chain - Liming Chen; Fengjun Lu; Xiaohong Lee (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: The purpose of this paper investigates the subject behavior of Energy conservation and emission reduction (ECER) based on structured classification of the organization types of FLF supply chain, and explores reasonable behavior incentive mechanism for ECER of FLF supply chain in China. Design/methodology/approach: This paper classifies the organization subjects of FLF supply chain, and different characteristics of organization subjects are compared in detail. ECER behavior incentive mechanism modeling of FLF supply chain is explored by taking advantage of principal-agent model in view of asymmetry information. Incentives issue of different operating subjects is discussed as enlightenment of the model. Findings: Three types of the organization subjects of FLF supply chain in China have been identified as: loose organization, semi-compact organization and compact organization.Subjects of different types have different abilities to conduct ECER work. Government needs to propose differentiation polices of incentive compensation for different operating subjects, widen the gap of differentiated subsidies/rewards for different investment levels on ECER conducted by different operating subjects of FLF supply chain. Research limitations/implications: It will take long-term unremitting efforts to achieve the target of ECER work for FLF supply chain in China, the dynamic issues and simulation modeling on behavior incentive mechanism of ECER should be developed in future research. Practical implications: Clear understanding of structured classification of the organization subject types of FLF supply chain and the behavior incentive mechanism for ECER, will help government to improve the ECER work in an efficient and effective way. Originality/value: Research to behavior incentive mechanism of ECER has important theoretical value and practical significance. This paper contributes to distinguish three types of operating subjects of FLF supply chain in China, put forward the behavior incentive mechanism of ECER to support the government to improve the ECER work scientifically.
Keywords: 650; behavioral incentive; energy conservation; emission reduction; freshwater live fish; supply chain organization